2013
DOI: 10.1209/0295-5075/102/47002
|View full text |Cite
|
Sign up to set email alerts
|

Self-passivation of vacancies in α -PbO

Abstract: We introduce a self-passivation of single lead (Pb) and oxygen (O) vacancies in the α-PbO compound through formation of a Pb-O vacancy pair. The preferential mechanism for pair formation involves initial development of the single Pb vacancy which, by weakening the covalent bonding, sets up the crystal lattice for an appearance of the O vacancy. Binding of the Pb and O vacancies occurs through the ionization interactions. Since no dangling bonds appear at the Pb-O pair site, this defect has a minor effect on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Lead oxide or PbO has a rich history as a photoconductive material in imaging devices and additional applications of PbO may be potentially realised in the field of spintronics. In recent studies of Bershevich and Reznik on α-PbO, the low temperature polymorph of lead oxide, it is shown that magnetism can be induced by non-magnetic impurities situated at the interstitial sites between crystal layers [21,22]. α-PbO in its bulk form is thermodynamically stable at room temperature and has a layered structure, with a space group P 4/nmm − D [23].…”
Section: Introductionmentioning
confidence: 99%
“…Lead oxide or PbO has a rich history as a photoconductive material in imaging devices and additional applications of PbO may be potentially realised in the field of spintronics. In recent studies of Bershevich and Reznik on α-PbO, the low temperature polymorph of lead oxide, it is shown that magnetism can be induced by non-magnetic impurities situated at the interstitial sites between crystal layers [21,22]. α-PbO in its bulk form is thermodynamically stable at room temperature and has a layered structure, with a space group P 4/nmm − D [23].…”
Section: Introductionmentioning
confidence: 99%
“…1 (d)). Since each electron stays on its own orbital, Hund's rules dictate the ferromagnetic ordering of these electrons [18]. The spin-polarization energy defined as the energy difference between the spin-unpolarized and spin-polarized states is found to be E pol =0.235 eV that indicates the stable triplet ground state [18].…”
Section: Crystallographic Defects In α-Pbomentioning
confidence: 97%
“…For the Pb-poor/O-rich conditions, the interaction between I O and V Pb can potentially occur but because each localized state is occupied by two holes, such interaction is repulsive. Under equilibrium growth conditions, the formation energy of V Pb and V O would become comparable, indicating a possibility of their pairing as well [23]. This combination of defects is unique as it induces vanishing of the dangling bonds and, therefore, occurs without generation of a defect state inside the band gap.…”
Section: Formation Energy Of Defectsmentioning
confidence: 97%
See 1 more Smart Citation